2003
DOI: 10.1002/hed.10277
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic transformation of thyroid cancer: Review of clinical, pathologic, and molecular evidence provides new insights into disease biology and future therapy

Abstract: It is based on an understanding of this process that effective treatments for this aggressive malignancy are currently being developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
55
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 86 publications
3
55
0
4
Order By: Relevance
“…25 At the other end of the spectrum, anaplastic thyroid carcinoma is morphologically undifferentiated, clinically aggressive, and fatal in most cases notwithstanding hard-hitting multimodality therapy. 1,2 The relationship between well-differentiated and undifferentiated thyroid carcinoma has long been a point of interest. The current consensus holds that most, if not all, anaplastic thyroid carcinomas arise from a pre-existing well-differentiated thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…25 At the other end of the spectrum, anaplastic thyroid carcinoma is morphologically undifferentiated, clinically aggressive, and fatal in most cases notwithstanding hard-hitting multimodality therapy. 1,2 The relationship between well-differentiated and undifferentiated thyroid carcinoma has long been a point of interest. The current consensus holds that most, if not all, anaplastic thyroid carcinomas arise from a pre-existing well-differentiated thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In reported series, anywhere from 8 to 90% of anaplastic thyroid carcinomas are seen in association with a differentiated carcinoma. 1,3 The direct and casual relationship between well-differentiated and undifferentiated thyroid carcinoma, however, has not been convincingly confirmed at the molecular genetic level. With their complex karyotypes and extensive allelic imbalances, anaplastic thyroid carcinomas show little resemblance to well-differ- entiated thyroid carcinoma, leading some investigators to conclude that anaplastic thyroid carcinomas arise de novo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very few anaplastic thyroid cancer patients survive longer than a year, and report of longterm survivors casts doubt on the validity of their diagnosis [5,6]. Passler and coworkers [7] found that irrespective of the surgical approach used, 5-year survival rate ranges from 4% to 8%.…”
Section: Discussionmentioning
confidence: 99%